Presence of an extended duplication in the putative low-density-lipoprotein receptor-binding domain of apolipoprotein B. Cloning and characterization of the domain in salmon. - Babin, P. J.; Deryckere, F.; Gannon, F. (HAL CCSD, 1995)
The sequence of the C-terminal 1058 amino acids of atlantic salmon (Salmo salar) apolipoprotein (apo) B was deduced from the nucleotide sequence of cloned cDNA. In comparison with chicken or mammals apoB-100, salmon apoB is C-terminally truncated and extended gaps are found. The two clusters of positively charged residues, previously identified as part of the putative low-density-lipoprotein (LDL) receptor-binding domain of apoB, are brought into close proximity in salmon apoB. This is achieved by the absence between the two clusters of the proline-rich area with the potential to form an amphipathic beta sheet, present in higher vertebrates. In addition, analysis of apoB amino acid sequences currently available in vertebrates revealed the presence of an extended internal duplication in the putative LDL receptor-binding domain. Thus, the two basic clusters would have been duplicated resulting in the presence, except for salmon apoB, of two homologous sites in the C-terminal part of the molecule. The results described here together with earlier biochemical and genetic evidence support the view that Arg3500, a residue mutated in familial defective apoB-100, could be included in a folded critical region of the putative LDL receptor-binding domain of human apoB-100. This region possibly brings the two sub-domains that arise from the duplication close to each other.